The Virtual Co-Actor: The Social Simon Effect does not Rely on Online Feedback from the Other - Vlainic, Elize; Liepelt, Roman; Colzato, Lorenza S.; Prinz, Wolfgang; Hommel, Bernhard (Frontiers in Psychology, 2010)
The social Simon effect (SSE) occurs if two participants share a Simon task by making a Go/No-Go response to one of two stimulus features. If the two participants perform this version of the Simon task together, a Simon effect occurs (i.e., performance is better with spatial stimulus–response correspondence), but no effect is observed if participants perform the task separately. The SSE has been attributed to the automatic co-representation of the co-actor's actions, which suggests that it relies on online information about the other's actions. To test this implication, we investigated whether the SSE varies with the presence and amount of online action-related feedback from the other person. Experiment 1 replicated the SSE with auditory stimuli. Experiment 2, in which participants were blindfolded, demonstrated that visual feedback from the other's actions is not necessary for the SSE to occur. Experiment 3 replicated Experiment 2 with a regular and a soundless keyboard. A comparable SSE was obtained in both conditions, suggesting that even auditory online input from the other's actions is not necessary. Taken together, our data suggest that the SSE does not rely on online information about the co-actor's actions but that a priori offline information about another actor's presence is sufficient to generate the effect.